Итоги цивилизационного развития человечества - Павленко, Ю. (Социология: теория, методы, маркетинг, 2000)
The article explores the perspectives of the global development in the beginning of the new millenium by analysing the general tendencies of history and its civilization variety. The author concludes that nowadays the future of different regions depends on their ability to adapt modern world’s achievements (in science, technology, organization etc.) to their national and cultural foundations. He supposes that in the XXI-st century there will be two global rival centres with leading roles — West (North America — Western Europe) and Far East (Japan — China). The chances of transition to the stage of information society in other regions are estimated as dubious.